Autophagy Stimulus Promotes Early HuR Protein Activation and p62/SQSTM1 Protein Synthesis in ARPE-19 Cells by Triggering Erk1/2, p38MAPK, and JNK Kinase Pathways. (8th February 2018) - Marchesi, Nicoletta; Thongon, Natthakan; Pascale, Alessia; Provenzani, Alessandro; Koskela, Ali; Korhonen, Eveliina; Smedowski, Adrian; Govoni, Stefano; Kauppinen, Anu; Kaarniranta, Kai; Amadio, Marialaura
Abstract : RNA-binding protein dysregulation and altered expression of proteins involved in the autophagy/proteasome pathway play a role in many neurodegenerative disease onset/progression, including age-related macular degeneration (AMD). HuR/ELAVL1 is a master regulator of gene expression in human physiopathology. In ARPE-19 cells exposed to the proteasomal inhibitor MG132, HuR positively affects at posttranscriptional level p62 expression, a stress response gene involved in protein aggregate clearance with a role in AMD. Here, we studied the early effects of the proautophagy AICAR + MG132 cotreatment on the HuR-p62 pathway. We treated ARPE-19 cells with Erk1/2, AMPK, p38 MAPK, PKC, and JNK kinase inhibitors in the presence of AICAR + MG132 and evaluated HuR localization/phosphorylation and p62 expression. Two-hour AICAR + MG132 induces both HuR cytoplasmic translocation and threonine phosphorylation via the Erk1/2 pathway. In these conditions, p62 mRNA is loaded on polysomes and its translation in de novo protein is favored. Additionally, for the first time, we report that JNK can phosphorylate HuR, however, without modulating its localization. Our study supports HuR's role as an upstream regulator of p62 expression in ARPE-19 cells, helps to understand better the early events in response to a proautophagy stimulus, and suggests that modulation of the autophagy-regulating kinases as potential therapeutic targets for AMD may be relevant.